2021
DOI: 10.48550/arxiv.2108.03726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Inference from Simple Instruments through Compliance Estimation

Stephen Coussens,
Jann Spiess

Abstract: Instrumental variables (IV) regression is widely used to estimate causal treatment effects in settings where receipt of treatment is not fully random, but there exists an instrument that generates exogenous variation in treatment exposure. While IV can recover consistent treatment effect estimates, they are often noisy. Building upon earlier work in biostatistics (Joffe and Brensinger, 2003) and relating to an evolving literature in econometrics (including Abadie et al., 2019;Huntington-Klein, 2020;Borusyak an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A value of less than 1-0.5 for instance-could mean that the school has a 50% likelihood of receiving a full-time SRO or that the school has a 100% likelihood of sharing a single SRO with another school. We can use this measure to estimate an "interacted RD" model that interacts the above-discontinuity indicator with our compliance measure to strengthen the first stage prediction of school SRO presence (Caetano et al, 2021;Coussens & Spiess, 2021;Huntington-Klein, 2020). Coussens & Spiess (2021) showed that an interacted model estimates a "super local average treatment effect" (SLATE), in our case giving more weight to schools for which the agency explicitly requests more SROs.…”
Section: Empirical Strategymentioning
confidence: 95%
See 2 more Smart Citations
“…A value of less than 1-0.5 for instance-could mean that the school has a 50% likelihood of receiving a full-time SRO or that the school has a 100% likelihood of sharing a single SRO with another school. We can use this measure to estimate an "interacted RD" model that interacts the above-discontinuity indicator with our compliance measure to strengthen the first stage prediction of school SRO presence (Caetano et al, 2021;Coussens & Spiess, 2021;Huntington-Klein, 2020). Coussens & Spiess (2021) showed that an interacted model estimates a "super local average treatment effect" (SLATE), in our case giving more weight to schools for which the agency explicitly requests more SROs.…”
Section: Empirical Strategymentioning
confidence: 95%
“…We can use this measure to estimate an "interacted RD" model that interacts the above-discontinuity indicator with our compliance measure to strengthen the first stage prediction of school SRO presence (Caetano et al, 2021;Coussens & Spiess, 2021;Huntington-Klein, 2020). Coussens & Spiess (2021) showed that an interacted model estimates a "super local average treatment effect" (SLATE), in our case giving more weight to schools for which the agency explicitly requests more SROs. 18 Intuitively, there is more information in observations for schools where the agency says with certainty that one or more SROs will be placed than in a school that we expect to share a new SRO with several other schools.…”
Section: Empirical Strategymentioning
confidence: 95%
See 1 more Smart Citation
“…There are, however, extensions of the standard IV estimator that attempt to improve estimation efficiency. Weighted IV methods [3,15,22] use predicted compliance to weight both treatment and control groups when computing the LATE estimator. Our method is similar in that we also use predicted compliance or triggering probabilities, but whereas the weighted IV estimator is unbiased for LATE only when there is no correlation between treatment effect heterogeneity and compliance, our estimator is unbiased for ITT (and asymptotically unbiased for LATE after dividing by the triggering rate) as long as the augmentation term that we construct equals zero in expectation.…”
Section: Related Workmentioning
confidence: 99%
“…In practice, we recommend using bootstrap [8] to estimate Cov(Δ(𝑌 ), τ0 ) and Var( τ0 ), and to refit the triggering probability model for each bootstrap sample. We can then estimate 3 the variance of 𝜏 𝑡𝑟𝑔1 with…”
Section: 21mentioning
confidence: 99%